Diagnostic Significance of Ischemia-Modified Albumin, S100b, and Neuron-Specific Enolase in Acute Ischemic Stroke - Altunayoglu Cakmak, Vildan; Gunduz, Abdulkadir; Karaca, Yunus; Alioglu, Zekeriya; Mentese, Ahmet; Topbas, Murat (Eurasian journal of emergency medicine, 2014)
Objective: Use of biochemical markers of cerebral ischemia is a newly favored approach for early diagnosis of ischemic stroke. Our aim was to establish the sensitivity and specificity of ischemia-modified albumin (IMA) in acute ischemic stroke and to compare it with S100b and neuron-specific enolase (NSE). We also intended to investigate the usefulness of a panel composed of these three biomarkers in acute ischemic stroke. Material and Methods: Consecutive adult patients who were admitted to the emergency department with focal neurological deficits were enrolled. Serum samples were obtained at the initial examination, and IMA, S100b, and NSE were measured. Receiver operating characteristics (ROC) curve analysis was used to determine the cut-off values of the biomarker and biomarker groups. Results: Serum IMA, NSE, and S100b levels were significantly higher in ischemic stroke patients (p<0.001, p=0.005, p=0.001, respectively). The optimum diagnostic cutoff point for IMA was 0.31 ABSU with 90% sensitivity and 57% specificity; 18 µg/L for NSE with 61% sensitivity and 53% specificity; and 65 pcg/l for S100b with 87% sensitivity and 72% specificity. With a combination of IMA with either S100b or NSE, instead of IMA alone, the best results were obtained with IMA and S100b, at 97% sensitivity and 37% specificity. Conclusion: This study indicates that IMA was a sensitive diagnostic biomarker in the acute phase of ischemic stroke, although its specificity is low. The combination of IMA with S100b and NSE did not add any beneficial effect to the specificity of IMA alone. (JAEM 2014; 13:112-7) Key words: Ischemic stroke, ischemic modified albumin, S100 calcium-binding protein beta subunit, neuron-specific enolase, biomarker